Advocating Students' Resilience in STEM Subjects in Tertiary Institutions - Josephine Ese Konyeme (Educare: Journal Educational and Multimedia, 2025)
Resilience in Science, Technology, Engineering, and Mathematics (STEM) education has become an essential attribute for students in tertiary institutions. Resilience is essential for students in Science, Technology, Engineering, and Mathematics (STEM) education due to the challenging nature of these fields. It enables students to persist through difficult coursework, handle academic pressure, and overcome failures, ultimately leading to academic success. Promoting resilience helps students manage stress, maintain mental health, and engage with complex STEM concepts. With the increasing complexity and challenges of STEM subjects, students often face academic, emotional, and psychological difficulties that can hinder their success. This paper advocates for promoting resilience among students in STEM disciplines by exploring strategies to enhance their ability to adapt, overcome challenges, and maintain motivation. The discussion focuses on the importance of resilience, challenges in STEM education, and strategies for fostering a resilient mindset among students. Key recommendations for fostering resilience in STEM students include promoting a growth mindset, incorporating mentorship programs, and encouraging collaborative learning. Growth mindset initiatives help students view challenges as learning opportunities, while mentorship provides guidance and emotional support. Collaborative learning reduces isolation and promotes teamwork, which boosts resilience. Additionally, institutions should provide mental health resources, support underrepresented groups in STEM, and integrate real-world applications into the curriculum. Flexible assessment methods that allow students to learn from mistakes are also important, as they encourage a positive attitude toward failure. By creating a culture of resilience through policies and leadership, tertiary institutions can equip students with the skills they need to succeed academically and in their future STEM careers.